Lesbian, gay or bisexual identity as a risk factor for trauma and mental health problems in Northern Irish students and the protective role of social support - Travers, Áine; Armour, Cherie; Hansen, Maj; Cunningham, Twylla; Lagdon, Susan; Hyland, Philip; Vallières, Frédérique; McCarthy, Angela; Walshe, Catherine (European journal of psychotraumatology, 2020)
Background: People identifying as lesbian, gay or bisexual (LGB) have been shown to experience more trauma and poorer mental health than their heterosexual counterparts, particularly in countries with discriminatory laws and policies. Northern Ireland is a post-conflict region with high rates of trauma and mental health problems, as well as significant levels of prejudice against the LGB community. To date, no studies in Northern Ireland have compared trauma exposure, social support and mental health status of LGB students to their heterosexual peers. Objective: The present study aimed to assess whether LGB status was associated with more trauma exposure and poorer mental health, and whether social support mediated these associations. Method: The sample was comprised of 1,116 university students. Eighty-nine percent (n = 993) identified as heterosexual and 11% (n = 123) identified as LGB. Path analysis was used to test the hypotheses. Results: LGB status was significantly associated with increased trauma exposure and with symptoms of PTSD, depression and anxiety, but not with problematic alcohol use. These associations were mediated by social support from family only. Conclusions: These results evidence vulnerabilities among Northern Irish students identifying as LGB in relation to trauma and mental health compared with their heterosexual peers. However, social support from family has the potential to mitigate risk. Educational initiatives should raise awareness of the importance of familial support for LGB youth, and those young people who lack family support should be considered an at-risk group, warranting particularly intensive targeting by relevant supports.